ECHO OF THE BATTLE OF KOŠARE AND PAŠTRIK IN SERBIAN CULTURE - Миљковић Матић, Јелена (Political Review, 2025)
A series of battles from 1999, on the border between Serbia and Albania, is commonly known among the people by the name of the first Battle that occurred chronologically, which is the Battle at the border post of Košare – also referred to as the Battle of Košare, or simply Košare. The Battle became widely known, and its fame has not diminished in the public’s memory to this day. The remembrance of Košare has materialized in a series of artistic and other symbolic creations. Here, we analyze those that were created before official institutions took part in preserving the memory of the Battle. Because these works were created on the initiative and efforts of the people, we consider them part of popular culture. They achieve two goals: the primary goal is the cultivation of the memory of the Battle and its participants; the secondary goal is to give a broader, national, and symbolic meaning to Košare as a historical event, thus elevating it from a worldly to a spiritual reality, qualifying it for inclusion in the system of Serbian identity traditions. Among these traditions is one of the most prominent, the tradition of the Battle of Kosovo, or the Kosovo cultural myth, to which the story of Košare seeks to connect. The mythologization of the historical event lasts for a long time, so we are now witnessing the beginning of that process, of which we do not know how it will unfold. Only future generations will be able to say whether the process of mythologizing Košare has been completed to the point where the Battle has transformed from a historical event into a national myth, or if, at some point, the transformation from historical to mythological event stagnated, in which case the Battle of Košare and Paštrik would be remembered as one among many significant and glorious battles in Serbian history.